Synthesis and Structural Characterization of Four Different Concentrations of Ant Nest (Myrmecodia pendens) Collagen Membranes with Potential for Medical Applications - Carolina DN; Satari MH; Priosoeryanto BP; Susanto A; Sukotjo C; Kartasasmita RE (Dove Medical Press, 2024)
Dyah Nindita Carolina,1,2 Mieke Hemiawati Satari,3,* Bambang Pontjo Priosoeryanto,4,* Agus Susanto,1,* Cortino Sukotjo,5,* Rahmana Emran Kartasasmita6,* 1Department of Periodontology, Dental Faculty, Universitas Padjadjaran, Bandung, West Java, Indonesia; 2Doctoral Study Program, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 3Department of Oral Biology, Dental Faculty, Universitas Padjadjaran, Bandung, West Java, Indonesia; 4Division of Veterinary Pathology, School of Veterinary Medicine & Biomedical Sciences, IPB University, Bogor, West Java, Indonesia; 5Department of Restorative Dentistry, College of Dentistry, University of Illinois at Chicago, Chicago, IL, 60612, USA; 6Research Group of Pharmaceutical Chemistry, School of Pharmacy, Institut Teknologi Bandung, Bandung, 40132, Indonesia*These authors contributed equally to this workCorrespondence: Dyah Nindita Carolina, Department of Periodontology, Dental Faculty, Universitas Padjadjaran, Bandung, West Java, 40132, Indonesia, Tel +628156132636, Email dyah.nindita@unpad.ac.idPurpose: The purpose of this study was to synthesize and structurally characterize four ant nest membranes in four different concentrations and determine the best concentration that could potentially be used as an alternative material for the production of new collagen barrier membranes.Materials and Methods: Membranes were created by mixing ant nest extracts at various concentrations of 0.5%, 1%, 1.5%, and 2%, as well as collagen, chitosan, and Polyvinyl Alcohol (PVA) using a film casting. A Universal Testing Machine (UTM) was used to evaluate mechanical properties including elastic modulus, tensile strength, maximum elongation, elongation at break, and maximum force. Water absorption was performed, FTIR was used for functional group identification, and morphology was examined using SEM. Additionally, EDS was used to identify the composition and distribution of elements in membranes. Statistical analysis was conducted using ANOVA (analysis of variance) and post hoc testing with a significance level of p < 0.01 for quantitative data.Results: The results showed that the mechanical properties produced the following mean (standard deviation): elastic modulus 0.87 Mpa (0.11), tensile strength 16.32 N/mm2 (2.46), maximum elongation 4.96% (1.72), elongation at break 5.23% (1.87), and maximum force 22.50 N (5.06). The average water absorption capacity of all four membranes had a p-value < 0.01. FTIR spectrum showed various peaks corresponding to functional groups, while SEM results indicated a homogeneous mixture. EDS analysis confirmed that the addition of ant plant extract at 0.5%, 1%, and 1.5% resulted in the presence of elements C, O, and Ca. Meanwhile, membranes prepared with 2% concentration had a different composition, namely C, O, Ca, and Na.Conclusion: Increasing the concentration of ant nest affects the values of the membrane's mechanical properties parameters, including the elastic modulus (0.87 Mpa), tensile strength (16.32 N/mm2), maximum elongation (4.96%), elongation at break (5.23%), and maximum force (22.50 N). The average membrane absorption of water (p value < 0.01) was also affected. SEM images showed homogeneous mixing, and membrane EDS results consisted of C, O, and Ca composition. However, there was no effect on FTIR functional groups. The anthill membrane with a 1% concentration has the potential to serve as an alternative membrane in guided tissue regeneration.Keywords: ant nest, carp scales, herbs, chitosan, polyvinyl alcohol, PVA